2023
DOI: 10.1021/acs.est.2c09824
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria and Virus Inactivation: Relative Efficacy and Mechanisms of Peroxyacids and Chlor(am)ine

Abstract: Peroxyacids (POAs) are a promising alternative to chlorine for reducing the formation of disinfection byproducts. However, their capacity for microbial inactivation and mechanisms of action require further investigation. We evaluated the efficacy of three POAs (performic acid (PFA), peracetic acid (PAA), and perpropionic acid (PPA)) and chlor(am)ine for inactivation of four representative microorganisms (Escherichia coli (Gramnegative bacteria), Staphylococcus epidermidis (Gram-positive bacteria), MS2 bacterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 75 publications
7
18
0
Order By: Relevance
“…The reactivity of tryptophan with PFA is also in agreement with the reactivity of protein-like compounds (such as tryptophan and tyrosine) measured by fluorescence spectroscopy during the disinfection of WW . In addition, the lack of PFA consumption by tyrosine, glutamine, histidine, and glycine, indicating their lower reactivity, is consistent with the results of Wang et al, who reported rate constants lower than 0.1 M –1 s –1 for these amino acids at neutral pH (7.1).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The reactivity of tryptophan with PFA is also in agreement with the reactivity of protein-like compounds (such as tryptophan and tyrosine) measured by fluorescence spectroscopy during the disinfection of WW . In addition, the lack of PFA consumption by tyrosine, glutamine, histidine, and glycine, indicating their lower reactivity, is consistent with the results of Wang et al, who reported rate constants lower than 0.1 M –1 s –1 for these amino acids at neutral pH (7.1).…”
Section: Resultssupporting
confidence: 91%
“…Among the 9 amino acids, cysteine, methionine, and, to a lesser extent, tryptophan were the most reactive with PFA (Figure A). PFA was completely consumed by cysteine (RCR = 0), which is consistent with the high reactivity of cysteine with PAA and the recent findings by Wang et al, showing the higher reactivity of cysteine and methionine with PFA. The reactivity of tryptophan with PFA is also in agreement with the reactivity of protein-like compounds (such as tryptophan and tyrosine) measured by fluorescence spectroscopy during the disinfection of WW .…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…20 mL of regular or saline wastewater (Table S1, Text S1) was buffered with phosphate to the desired pH and spiked with 100 μM of PAA, PFA, or NaOCl in amber glass vials. It is worth noting that these three disinfectants provide comparable bacterial inactivation at the same dosage as demonstrated by our recent study . The reactors were protected from ambient light, stirred vigorously, and sealed with caps with a headspace less than 5 mL.…”
Section: Methodsmentioning
confidence: 89%